Analysis of Environmental Health Risks from Pesticide Exposure among Green Mustard Farmers in Ngkari-Ngkari Village, Baubau City - Sri Filda; Ramadhan Tosepu; Asramid Yasin (International Journal Of Health Science, 2025)
Ngkari-Ngkari Sub-district is an agricultural area that produces rice, fruits, and vegetables, particularly green mustard (caisin), with a population composed of diverse ethnic groups. The use of pesticides in agricultural activities may pose health risks when applied improperly. This study aims to analyze environmental health risks due to pesticide exposure among green mustard farmers in Ngkari-Ngkari, Baubau City. Plant samples were collected two days after chemical pesticide spraying using standard procedures and analyzed at the UHO Pharmacy Laboratory. A total of 64 farmers were selected through total sampling, and data were obtained using structured questionnaires. Data analysis employed SPSS and the Environmental Health Risk Assessment (EHRA) method. Laboratory results indicated that pesticide concentration in green mustard plants was 0 mg/kg/day or undetected. The estimated intake exposure among farmers was 0.000364 mg/kg/day, while the calculated risk quotient (RQ) of Chlorpyrifos exposure was 0.0121 mg/kg/day. An RQ value ≤ 1 suggests that the 64 farmers were not at risk of adverse health effects from exposure to Chlorpyrifos-based pesticides. This study concludes that pesticide use in Ngkari-Ngkari remains within safe limits for farmers, although continuous monitoring and proper application are necessary to prevent long-term cumulative risks. Limitations of this study include the influence of environmental factors during sampling and the potential effect of sample storage time, indicating the need for biological monitoring and soil condition evaluation in future studies to strengthen the findings.